2017
DOI: 10.1029/2017eo081839
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Pulse of the Planet

Abstract: How fast is Earth warming? Ocean heat content and sea level rise measurements may provide a more reliable answer than atmospheric measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 0 publications
0
55
0
Order By: Relevance
“…As such, the record of the global ocean heat content robustly represents the signature of global warming, as it is less impacted by weather-related noise and climate variability such as El Niño and La Niña events (Cheng et al, 2018). The IPCC (2013) has concluded that it is very likely that anthropogenic forcings have made a substantial contribution to the increase of global upper ocean heat content (0-700 m) since the 1970s.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…As such, the record of the global ocean heat content robustly represents the signature of global warming, as it is less impacted by weather-related noise and climate variability such as El Niño and La Niña events (Cheng et al, 2018). The IPCC (2013) has concluded that it is very likely that anthropogenic forcings have made a substantial contribution to the increase of global upper ocean heat content (0-700 m) since the 1970s.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A consequence is an energy imbalance at the top of the atmosphere (Trenberth et al, ; von Schuckmann et al, ) of which about 92% goes into the ocean, increasing OHC. Primary indicators of a changing climate include increases in global mean surface temperature, sea level, and OHC (Cheng et al, , ; Figure a). Moreover, OHC and sea level changes are more robust climate indicators with less weather noise, both for global averages (Cheng et al, ) and regional changes.…”
Section: Introductionmentioning
confidence: 99%
“…This heat imbalance is manifested by the increase of ocean heat content (OHC). Therefore, from the energy point of view, the most fundamental metric for global warming is EEI and OHC [17,18,27,28]. Also OHC is a robust metric for global warming since it is much less impacted by the natural fluctuations of the climate system than is GMST on inter-annual scales [27].…”
Section: Introductionmentioning
confidence: 99%